Dantha Bhagya Scheme-A Way Forward for People with Edentulism in India - Sabah Zubair; Sumit Kumar (Medsci Publications, 2022)
Abstract: Oral health problems are emerging as one of the major public health concerns. Elderly people have to face many difficulties in utilizing oral health services, especially the below-the-poverty-line population. Taking into Consideration Dantha Bhagya Yojana was launched in Karnataka, for the Below poverty line population as dental services are highly-priced. Databases, media articles, and government official websites providing information regarding Dantha Bhagya Yojana were considered. The scheme aims to provide complete and partial dentures to the senior citizens of Karnataka, belonging to the below poverty line category. The program works under public-private partnership lines and is proving to be helpful to the beneficiaries in Karnataka province. These services are made available in public as well as private dental colleges of Karnataka. The community healthcare workers' role is to identify the edentulous patients and refer them to the nearby dental college for treatment.